Exploration of Xi 'an city image communication strategy in new media era - Yiming Zhang; Che Ching Lai (Human Resource Management Academic Research Society, 2025)
The development of new media technology has changed urban image communication. As the core area of "The Belt and Road" and an important central city in the west, Xi'an's image communication is of great significance in the era of new media. Through qualitative analysis, this study explores the strategies and effects of Xi'an city image communication in the new media era. The research finds that although the noise of public opinion on new media brings information distortion and public cognitive bias, it also increases the exposure rate of Xi'an and provides new opportunities for the city image communication. In terms of content planning and communication strategies, "Xi'an Release" combines Xi'an's history, culture, economic development, and urban construction; enhances the effect of information dissemination through multi-platform linkage and interactive activities; and enhances the visibility and influence of Xi'an's urban image. The public's satisfaction with the content of the communication of Xi'an city image is positively correlated with its perception of the city image, and the satisfaction of different groups is different. Optimizing the content and form of communication is crucial to improving the public's satisfaction and perception of Xi'an ''s city image. This study aims to provide a theoretical basis and practical guidance for Xi'an to optimize its city image communication strategy, enhance its city image influence and soft power, and promote sustainable urban development.